Evaluation of pain in the critical patient adult: proposal for construction of a fluxogram based on scientific evidence: PROPOSAL FOR CONSTRUCTION OF A FLUXOGRAM BASED ON SCIENTIFIC EVIDENCE - Souza, Thais Gomes (2019)
This study aims to broaden the knowledge about the mechanisms of pain evaluation and the benefit of the nursing care traced, evaluating the application of the scales according to the patient adult profile found in the ICUs. There are two specific objectives: Describe the main validated scales for use in patients in the intensive care unit and the construction of a flowchart to choose the best scale according to the patient's profile. An integrative review was carried out to select pain assessment instruments and, from this, the construction of the flow chart. Beneficial results of great value were found to consolidate the knowledge about the mechanics of pain evaluation. We conclude that it is necessary to validate the flowchart elaborated in this research for implantation in the intensive care units, resulting in future evidence and improvement both in pain relief and in the reduction of the permanence of this client with several invasive devices, consequently reducing their hospitalization time.